Exercise twice‐a‐day potentiates markers of mitochondrial biogenesis in men. Issue 1 (2nd December 2019) - Andrade‐Souza, Victor Amorim; Ghiarone, Thaysa; Sansonio, Andre; Santos Silva, Kleiton Augusto; Tomazini, Fabiano; Arcoverde, Lucyana; Fyfe, Jackson; Perri, Enrico; Saner, Nicholas; Kuang, Jujiao; Bertuzzi, Romulo; Leandro, Carol Gois; et al.
Abstract: Endurance exercise begun with reduced muscle glycogen stores seems to potentiate skeletal muscle protein abundance and gene expression. However, it is unknown whether this greater signaling responses is due to performing two exercise sessions in close proximity—as a first exercise session is necessary to reduce the muscle glycogen stores. In the present study, we manipulated the recovery duration between a first muscle glycogen‐depleting exercise and a second exercise session, such that the second exercise session started with reduced muscle glycogen in both approaches but was performed either 2 or 15 hours after the first exercise session (so‐called "twice‐a‐day" and "once‐daily" approaches, respectively). We found that exercise twice‐a‐day increased the nuclear abundance of transcription factor EB (TFEB) and nuclear factor of activated T cells (NFAT) and potentiated the transcription of peroxisome proliferator‐activated receptor‐ɣ coactivator 1‐alpha (PGC‐1α), peroxisome proliferator‐activated receptor‐alpha (PPARα), and peroxisome proliferator‐activated receptor beta/delta (PPARβ/δ) genes, in comparison with the once‐daily exercise. These results suggest that part of the elevated molecular signaling reported with previous "train‐low" approaches might be attributed to performing two exercise sessions in close proximity. The twice‐a‐day approach might be an effective strategy to induce adaptations related to mitochondrial biogenesis and fat oxidation.